Chromosome Evolution in Dendropsophini (Amphibia, Anura, Hylinae) - Suarez, P.; Cardozo, D.; Baldo, D.; Pereyra, M. O.; Faivovich, J.; Orrico, V. G. D.; Catroli, G. F.; Grabiele, M.; Bernarde, P. S.; Nagamachi, C. Y.; Haddad, C. F. B. [UNESP]; Pieczarka, J. C. (Karger, 2013)
Dendropsophini is the most species-rich tribe within Hylidae with 234 described species. Although cytogenetic information is sparse, chromosome numbers and morphology have been considered as an important character system for systematic inferences in this group. Using a diversity of standard and molecular techniques, we describe the previously unknown karyotypes of the genera Xenohyla, Scarthyla and Sphaenorhynchus and provide new information on Dendropsophus and Lysapsus. Our results reveal significant karyotype diversity among Dendropsophini, with diploid chromosome numbers ranging from 2n = 22 in S. goinorum, 2n = 24 in Lysapsus, Scinax, Xenohyla, and almost all species of Sphaenorhynchus and Pseudis, 2n = 26 in S. carneus, 2n = 28 in P. cardosoi, to 2n = 30 in all known Dendropsophus species. Although nucleolar organizer regions (NORs) and C-banding patterns show a high degree of variability, NOR positions in 2n = 22, 24 and 28 karyotypes and C-banding patterns in Lysapsus and Pseudis are informative cytological markers. Interstitial telomeric sequences reveal a diploid number reduction from 24 to 22 in Scarthyla by a chromosome fusion event. The diploid number of X. truncata corroborates the character state of 2n = 30 as a synapomorphy of Dendropsophus. (C) 2013 S. Karger AG, Basel
Keywords: B chromosomes; Dendropsophini; Hylidae; Interstitial telomeric sequence; Karyotype diversity